2017
DOI: 10.1039/c7mb90021j
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Metabolomic profiling and biochemical evaluation of the follicular fluid of endometriosis patients

Abstract: Correction for ‘Metabolomic profiling and biochemical evaluation of the follicular fluid of endometriosis patients’ by Marianna Santonastaso et al., Mol. BioSyst., 2017, DOI: 10.1039/c7mb00181a.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…The results showed an increase in β-hydroxybutyric acid and glutamine and a decrease in tryptophan as well as an alteration of pathways such as nitrogen metabolism, pyrimidine metabolism, glutamine and glutamate metabolism, and aminoacyl-tRNA biosynthesis. Endometriosis can be considered an inflammatory disease with evidence of elevated levels of peritoneal fluid cytokines and growth factors, alterations in B cell activity, and an increased incidence of autoantibodies [18,29]. Furthermore, peritoneal macrophages are increased in number, concentration, and activity in women with the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed an increase in β-hydroxybutyric acid and glutamine and a decrease in tryptophan as well as an alteration of pathways such as nitrogen metabolism, pyrimidine metabolism, glutamine and glutamate metabolism, and aminoacyl-tRNA biosynthesis. Endometriosis can be considered an inflammatory disease with evidence of elevated levels of peritoneal fluid cytokines and growth factors, alterations in B cell activity, and an increased incidence of autoantibodies [18,29]. Furthermore, peritoneal macrophages are increased in number, concentration, and activity in women with the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In the last years, FF has been investigated as an ideal candidate for non-invasive method of oocyte selection in fertility clinics [29]. Metabolic profiling of FF has been applied to find biomarkers of oocyte developmental competence [30] and to find also specific panels of biomarkers related to some infertility pathologies [31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several studies have been carried out to determine the metabolic FF profile of women with infertility due to different causes. Using an untargeted metabolomic ap-proach, with the aid of high-resolution proton nuclear magnetic resonance ( 1 H-NMR) [9,10] or liquid/gas chromatography-mass spectrometry [5,11], it has been shown that alteration of some metabolites in the FF of infertile females (IF) were affected by PCOS [12], ROR [13] and EM [14,15]. Some metabolomic studies have even found significant differences in IF with negative IVF outcomes compared to IF with positive IVF outcomes [16][17][18].…”
Section: Introductionmentioning
confidence: 99%